Silent warfare understanding the world of intelligence - Shulsky, Abram N. (Brassey's, Inc., 2002)
A thoroughly updated revision of the first comprehensive overview of intelligence designed for both the student and the general reader, Silent Warfare is an insider's guide to a shadowy, often misunderstood world. Leading intelligence scholars Abram N. Shulsky and Gary J. Schmitt clearly explain such topics as the principles of collection, analysis, counterintelligence, and covert action, and their interrelationship with policymakers and democratic values. This new edition takes account of the expanding literature in the field of intelligence and deals with the consequences for intelligence of vast recent changes in telecommunication and computer technology the new "information age." It also reflects the world's strategic changes since the end of the Cold War. This landmark book provides a valuable framework for understanding today's headlines, as well as the many developments likely to come in the real world of the spy.